The Potential Of Land Use Objects In The Area Of Sanur Kaja Village As A Tourist Attraction - Suranata Putu Gede; Ni Komang Armaeni; I Wayan Gde Erick Triswandana (Jurnal Sutramas, 2022)
Green Open Space (RTH) has many functions besides ecological functions as the lungs of regions. Denpasar has at least 1,091.07 Ha of RTH where not all of its potential is utilized optimally for example the RTH in Sanur Kaja Village. The current condition in the green lane area or Green Open Space (RTH) in Sanur Kaja Village is that the green belt area is not organized due to lack of attention and lack of knowledge about the green line. Many semi-permanent buildings can be seen standing irregularly in the green open space on the deeper side of the area. Apart from semi-permanent buildings, there are also many buildings designated for residential houses and other business places such as shops, cafes or restaurants, and so on. The Village Topography, especially in the area of Jl. Hangtuah and Jl. Sedap Malam is a lowland area with an altitude of 0-7 meters ASL with the use of land as a RTH covering an area of approximately 39.4311 hectares following the RTRW document for Denpasar from the year 2011-2031. From the data collection using satellite imagery and field measurements, it was found that there were violations related to the construction of buildings with residential and business designations. The recorded violations cover an area of 11.6529 hectares, leaving approximately 27.7782 hectares of existing RTH that must be saved by carrying out development to later be transformed into a tourist attraction.